Graffiti, Street Art and Ambivalence - Graeme Lorenzo Evans (Humanities)
The article considers the practice and praxis of graffiti and street art from the perspectives of law enforcement, local government and placemaking, and between the production and consumption of this ambivalent form of cultural expression. The work is based on primary, site-based research and visualisation undertaken in Europe, North America and Australia.